2014
DOI: 10.2174/1567205011666140110112608
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functional Connectivity of the Marginal Division in Alzheimer’s Disease

Abstract: The marginal division (MrD) is a neostriatum subregion that links the limbic system and basal nucleus of Meynert; it is an important subcortical center that is involved in learning and memory. Alzheimer's disease (AD) is a neurodegenerative disorder and the most common cause of dementia in the elderly. AD clinically manifests as gradually progressive cognitive decline with behavioral disorders. Prior to full dementia, AD patients typically experience a transient state, i.e., mild cognitive impairment (MCI). Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 79 publications
3
22
0
Order By: Relevance
“…Data from some of the subjects examined in the present study have been reported in our previous studies of regional homogeneity , amygdalar connectivity , thalamic connectivity , and marginal division connectivity (Zhang et al, 2014) during resting states. All of the subjects met identical methodological stringency criteria, and comprehensive clinical details can be found in our prior work Zhang et al, 2012Zhang et al, , 2014Zhou et al, 2013).…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…Data from some of the subjects examined in the present study have been reported in our previous studies of regional homogeneity , amygdalar connectivity , thalamic connectivity , and marginal division connectivity (Zhang et al, 2014) during resting states. All of the subjects met identical methodological stringency criteria, and comprehensive clinical details can be found in our prior work Zhang et al, 2012Zhang et al, , 2014Zhou et al, 2013).…”
Section: Methodsmentioning
confidence: 82%
“…All of the subjects met identical methodological stringency criteria, and comprehensive clinical details can be found in our prior work Zhang et al, 2012Zhang et al, , 2014Zhou et al, 2013). Notably, all of the analyses attempted in this study are fully orthogonal to any previously published effects that are based on the AD and MCI replication samples and thus ensure the independence of the reported effects.…”
Section: Methodsmentioning
confidence: 98%
“… [76] c, †6235122372.48.527161169.26.5xx3.0 T GESBT Zhang et al. [77] c, †6235122372.48.527161169.26.5x3.0 T GESBMrD (l, r)Gour et al. [29]28146875.12.91441072.83.0xx3.0 T SSBPCC, perirhinal cortex (l, r), dlPFC (l, r)Weiler et al.…”
Section: Resultsmentioning
confidence: 99%
“…For example, gray matter (GM) atrophy of the cerebellum was detected in AD in several neuroimaging studies (Thomann et al, 2008; Bas et al, 2009). In addition, the AD patients exhibited significantly lower cerebral blood flow (CBF; Hauser et al, 2013), abnormal activation during Stroop tests (Kaufmann et al, 2008) and impaired rsFCs of the cerebellum (Wang et al, 2007; Zhang et al, 2014) in several studies. Furthermore, the AD pathological changes have now been revealed in the cerebellum including deposits of amyloid-β plaques, neurofibrillary tangles, increased microglia and so on (Larner, 1997; Ciavardelli et al, 2010; Sepulveda-Falla et al, 2011).…”
Section: Introductionmentioning
confidence: 99%